Association between variants of neuromedin U gene and taste thresholds and food preferences in European children: Results from the IDEFICS study. (1st November 2019) - Grippi, Claudio; Ahrens, Wolfgang; Buchecker, Kirsten; Chadjigeorgiou, Charalambos; De Henauw, Stefaan; Koni, Anna C.; Foraita, Ronja; Lissner, Lauren; Molnár, Denés; Moreno, Luis A.; Pitsiladis, Yannis; Reisch, Lucia A.; et al.
Abstract: Aim: The neuropeptide neuromedin U (NMU) known for its role in appetite, feeding and energy balance could be involved in the control of food choice and taste sensitivity. We examined the association between NMU polymorphisms/haplotypes and taste thresholds and food preferences in a population of European children. Methods: A total of 578 subjects from the IDEFICS study (mean age 7.5 ± 0.8 SD, boys 53.6%) with NMU genotype data and food preference (salty, fatty, sweet, flavour and umami food) and taste threshold (salt, fat, sweet, umami) tests available were analysed. Three single nucleotide polymorphisms (SNPs; rs6827359, T:C; rs12500837, T:C; rs9999653, C:T) of NMU gene were analyzed and five major haplotypes were inferred. The associations between genotypes and food preferences or taste thresholds were investigated (odds ratios –OR, adjusted for age, sex and country). A p  < 0.05 after false discovery rate adjustment ( p FDR) was considered statistically significant. Results: The association between NMU genotypes and food preference showed two NMU SNPs associated with preference for food containing sodium glutamate (umami taste; rs6827359C, OR = 1.61, 95% confidence interval (CI):1.20–2.17; rs9999653T, OR = 1.59, 95%CI:1.18–2.13). In the haplotype analysis, the CTT haplotype showed an OR of 1.70 (95%CI:1.16–2.5) for the umami food preference, while CCT haplotype showed an OR of 1.63 (95%CI:1.11–2.40), compared to the most frequent haplotype (TTC). Carriers of CCT/CCT vs subjects with no CCT haplotype showed an OR of 4.78 (95%CI:1.86–12.30). Umami food preference was associated with low values of BMI z -score, arm circumferences, skinfolds and fat mass ( p FDR<0.05). No association between NMU genetic variants and taste thresholds was found. Conclusions: This study shows for the first time in children an association between preference for umami food and a NMU haplotype, previously found associated with low BMI values.